2017
DOI: 10.1002/macp.201600593
|View full text |Cite
|
Sign up to set email alerts
|

The Deeply Understanding of the Self‐Healing Mechanism for Self‐Healing Behavior of Supramolecular Materials Based on Cyclodextrin–Guest Interactions

Abstract: Cyclodextrin (CD)‐based host–guest interactions are one of the important supramolecular interactions and have been playing significant role in the design of self‐healing materials due to high selectivity and dynamic equilibrium. However, a deeper understanding of the self‐healing mechanism is still rare, although self‐healing materials based on CD–guest interactions have many advantages. This study provides a first step for the fundamental understanding of the influence factors on self‐healing behavior of mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In this paper, the host–guest interactions were chosen as dynamic healing motifs to endow self-healing ability to materials because they are stable in moisture conditions and then the self-healing of the resulting material is not affected by surface ageing. The synthesis procedure of DN elastomer is shown is Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, the host–guest interactions were chosen as dynamic healing motifs to endow self-healing ability to materials because they are stable in moisture conditions and then the self-healing of the resulting material is not affected by surface ageing. The synthesis procedure of DN elastomer is shown is Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…Such transient bonds are in the dynamic equilibrium between associated and dissociated states. Consequently, supramolecular polymer networks response to the external stimuli and have potential to use for designing electronic, optic‐electronic, drug‐delivery, and/or self‐healing materials. The supramolecular polymer networks are divided in 2 general types.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that sufficient polymer chains mobility, a small amount of water, and high inclusion constant of host-guest interactions were essential to the self-healing process for this kind of composites [45].…”
Section: Self-healing Composites Based On Cd-guest Interactionsmentioning
confidence: 99%